A Case of Treatment with Steroid and Hydrochloroquine of Thrombocytopenia in Primary Sjögren's Syndrome - Yeong Seop Yun; Ji Wook Choi; Young Jae Doo; Tae Hyung Kim; Hye Lim Oh; Ji Min Oh (Kosin Medical Journal, 2017)
Sjögren's syndrome is a systemic autoimmune disease characterized by sicca symptoms and extraglandular manifestations. Anemia, leukopenia, thrombocytopenia and lymphoproliferative disorders are well-known extraglandular, hematological complications of Sjögren's syndrome. These hematologic alterations are usually mild and respond well with steroid therapy. We report a case of a 52-year-old female patient who was initially presented with thrombocytopenia. The patient was then diagnosed with primary Sjögren's syndrome and initially treated with steroid. The patient's platelet count was decreased when steroid was tapered. The dose of steroid could be effectively reduced after combined medication with hydroxychloroquine.